Down-regulation of microRNA-142-3p inhibits the aggressive phenotypes of rheumatoid arthritis fibroblast-like synoviocytes through inhibiting nuclear factor-κB signaling. Issue 7 (8th July 2019) - Qiang, Jianhong; Lv, Tingting; Wu, Zhenbiao; Yang, Xichao
Abstract : The present study aimed to investigate the regulatory roles of miR-142-3p on the aggressive phenotypes of rheumatoid arthritis (RA) human fibroblast-like synoviocytes (RA-HFLSs), and reveal the potential mechanisms relating with nuclear factor-κB (NF-κB) signaling. miR-142-3p expression was detected in RA synovial tissues and RA-HFLSs by quantitative real-time PCR (qRT-PCR) and Northern blot analysis. RA-HFLSs were transfected with miR-142-3p inhibitor and/or treated with 10 µg/l tumor necrosis factor α (TNF-α). The viability, colony formation, apoptosis, migration, invasion, and the levels of interleukin (IL)-6, and matrix metalloproteinase 3 (MMP-3) were detected. The mRNA expressions of B-cell lymphoma-2 (Bcl-2), Bax, Bad, IL-6, and MMP-3 were detected by qRT-PCR. Moreover, the expression of Bcl-2, IL-1 receptor-associated kinase 1 (IRAK1), Toll-like receptor 4 (TLR4), NF-κB p65, and phosphorylated NF-κB p65 (p-NF-κB p65) were detected by Western blot. The interaction between IRAK1 and miR-142-3p was identified by dual luciferase reporter gene assay. MiR-142-3p was up-regulated in RA synovial tissues and RA-HFLSs. TNF-α activated the aggressive phenotypes of RA-HFLSs, including enhanced proliferation, migration, invasion, and inflammation, and inhibited apoptosis. miR-142-3p inhibitor significantly decreased the cell viability, the number of cell clones, the migration rate, the number of invasive cells, the contents and expression of IL-6 and MMP-3, and increased the apoptosis rate and the expressions of Bax and Bad, and decreased Bcl-2 expression of TNF-α-treated RA-HFLSs. MiR-142-3p inhibitor significantly reversed TNF-α-induced up-regulation of IRAK1, TLR4, and p-NF-κB p65 in TNF-α-treated RA-HFLSs. Besides, IRAK1 was a target of miR-142-3p. The down-regulation of miR-142-3p inhibited the aggressive phenotypes of RA-HFLSs through inhibiting NF-κB signaling.